Ferric Phosphate Hydroxide Microcrystals for Highly Efficient Visible‐Light‐Driven Photocatalysts. Issue 11 (18th June 2013) - Wang, XiaoJin; Pang, Huan; Zhao, Shanshan; Shao, Weifang; Yan, Bo; Li, Xinran; Li, Sujuan; Chen, Jing; Du, Weimin
Abstract Fe4(OH)3(PO4)3 microcrystals are successfully synthesized by a simple hydrothermal method. Due to a possible self‐etching mechanism, different morphologies of Fe4(OH)3(PO4)3 microcrystals are obtained. Several reactions with different temperatures and times are performed to confirm the supposed self‐etching mechanism. Moreover, as a result of their different micro/nanostructures, these microcrystals present different photocatalytic activities for visible‐light‐driven photodegragadation of methylene blue.